Improving the relationship between the University and the community: The case of the University of Montemorelos - Gregorutti, Gustavo (2013)
The idea of the university in Latin America has been strongly influenced by European models that were perpetuated since the arrival of the colonizers. As a result, the university activity was conceived in special places where students learned about  certain topics and then return to the real world. In recent years, there has been a growing concern in various groups of scholars and public leaders for the relevance of the impact that universities are having on their communities. This study focuses on Montemorelos University and its impact on the surrounding communities. This study also reveals examples of how community involvement can be a key factor in higher education.